Children’s Acquisition of wh-questions in Najdi Arabic - Amal S Almuqbil; Yasser Albaty (International Journal of Linguistics, Literature and Translation, 2025)
This study investigates the acquisition of subject wh-questions (Sub-WQs) and object wh-questions (Obj-WQs) in Najdi Arabic (NA). Drawing on a truth value judgment task (TVJT), the study tested 21 NA-speaking children aged 3 to 6 divided into three age groups, focusing on their comprehension of Sub-WQs and Obj-WQs using two wh-phrases: mi:n ‘who’ and ʔæj ‘which.’ Findings revealed that children comprehended Sub-WQs significantly better than Obj-WQs, supporting previous research in languages with overt wh-movement. In contrast, no significant difference emerged between mi:n and ʔæj, suggesting that both wh-phrases are equally accessible to NA-speaking children. Additionally, age did not significantly impact performance, indicating early acquisition of both question types across the tested age range. These results challenge the Antecedent Government Hypothesis and support the notion that syntactic movement and morphological simplicity shape acquisition patterns. The study contributes to the growing body of research on wh-question acquisition and highlights the need for further cross-linguistic and developmental investigations.